Trends and Factors Associated With Risk Perception, Anxiety, and Behavior From the Early Outbreak Period to the Controlled Period of COVID-19 Epidemic: Four Cross-Sectional Online Surveys in China in 2020 - Liu, Bei; Liu, Hanyu; Han, Bingfeng; Zhao, Tianshuo; Sun, Tao; Tan, Xiaodong; Cui, Fuqiang (Frontiers in Public Health, 2022)
Background: The first wave of the COVID-19 epidemic in China was brought under with 3 months- from mid-January 2020 to the end of March 2020. This study aims to examine perceived risk, anxiety and behavioral response of the general public related to the outbreak of COVID-19 in four cross-sectional surveys conducted throughout China. Methods: In 2020, four cross-sectional, population-based online survey were conducted from January 28 to February 3, from February 10 to 12, from February 20 to 22, and from March 1 to 10, respectively. Convenience sampling was used for recruiting survey participants. The four independent online questionnaires were sent from the same approach (WeChat and MicroBlog), and anyone who receives the questionnaire on the Internet or mobile phone and meets the inclusion criteria could fill in it. The same questionnaires repeatedly used in the four surveys. Wilcoxon signed ranks test was used to compare people’s perceived risk, anxiety and protective behaviors changes in four stages. General linear model was used to identify associations between some demographic factors and perceived risk, anxiety scores, and protective behaviors. Results: The proportion of high perceived risk has dropped from 24.7% to 4.7%. The proportion of people wore masks when they went out has increased from 97.0% to 98.3%. People at age 30-39 years, with high-degree education, with married status, and accompanied with poor self-rated health status were prone to have higher risk perception and anxiety. Anxiety levels had stronger associations with adoption of protective behaviors in the early epidemic periods than in the late epidemic periods. Conclusions: The levels of perceived risk and anxiety showed a trend of rising first and then falling. Gradually upward trend on initiative preventive behaviors including wearing mask and avoiding visiting crowded places also was observed through scanning data at four stages. People at age 30-39 years, with high-degree education, and accompanied with poor self-rated health status were prone to have higher risk perception and anxiety. Our findings showed that people simultaneously presented both high-level risk perception and anxiety across the four wave surveys, leading to their positive self-prevention and protective behavior.